STRATEGI PENGUATAN PENGEMBANGAN KOMPETENSI PNS MELALUI KONSEP SMART TRAINING DI BPSDM KEMENTERIAN DALAM NEGERI - Hariawan Bihamding (Bajang Institute, 2024)
The government apparatus is an essential element in this country whose functions are as a dynamist and catalyst for driving development, public services, and governance management at large. The success or failure of achieving state goals is mainly determined by the commitment, quality, and competence of its apparatus. It is necessary to realize that the development of civil servant competency has not currently achieved optimal results, there are many obstacles faced, especially funding and output problems or achievement of results that have not met expectations. These become the reason for the author to conduct research entitled